2020
DOI: 10.1186/s43058-020-00090-w
|View full text |Cite
|
Sign up to set email alerts
|

Importance of congruence between communicating and executing implementation programmes: a qualitative study of focus group interviews

Abstract: Background The Ostrobothnia Depression Programme (ODP) in Finland was intended to implement two evidence-based brief psychotherapy interventions, namely motivational interview and behavioural activation, in several regional psychiatric teams. A simultaneous effectiveness study was conducted. Considerable tension was encountered between these two arms, causing resistance to change. We conducted a qualitative case study to better understand this tension and to discuss how managerial and executive practices may e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Leaders who develop a strong organizational culture, clear expectations, and provide support, experience more success with program implementation (Arnold et al, 2020;Bunger et al, 2019). Lindholm et al (2020) identify the role and performance of leadership to "be critical for the success of a programme and also for sustaining its outcomes" (p. 2); they also assert the importance of leadership in establishing shared goals and a clear plan to achieve them as key factors to successful program implementation. Johnson et al (2017) found that teachers who feel supported by their administration and who feel competent in their ability were more open to adopting new teaching practices.…”
Section: The Power Of Leadership In Program Implementationmentioning
confidence: 99%
“…Leaders who develop a strong organizational culture, clear expectations, and provide support, experience more success with program implementation (Arnold et al, 2020;Bunger et al, 2019). Lindholm et al (2020) identify the role and performance of leadership to "be critical for the success of a programme and also for sustaining its outcomes" (p. 2); they also assert the importance of leadership in establishing shared goals and a clear plan to achieve them as key factors to successful program implementation. Johnson et al (2017) found that teachers who feel supported by their administration and who feel competent in their ability were more open to adopting new teaching practices.…”
Section: The Power Of Leadership In Program Implementationmentioning
confidence: 99%